2018
DOI: 10.4082/kjfm.2018.39.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Boric Acid as a Treatment of Choice for Chronic Suppurative Otitis Media and Its Ototoxicity

Abstract: Chronic suppurative otitis media (CSOM) is one of the most common chronic infectious diseases worldwide, especially affecting children. The patients or the parents of the affected children are often worried about the cost of medical visits, prescription medicines, or inconsistently effective medication. The complications of CSOM have been greatly reduced because of the development of antibiotics; however, the irrational use of antibiotics has led to the emergence of organisms resistant to the commonly used dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Two review studies concluded that topical boric acid was effective in the treatment of chronic otitis media and vulvovaginal candidiasis. [31,32] Boric acid has not been investigated as a potential anti-adhesion agent ever before.…”
Section: Discussionmentioning
confidence: 99%
“…Two review studies concluded that topical boric acid was effective in the treatment of chronic otitis media and vulvovaginal candidiasis. [31,32] Boric acid has not been investigated as a potential anti-adhesion agent ever before.…”
Section: Discussionmentioning
confidence: 99%
“…In some clinical studies, boric acid was also used for treating chronic suppurative otitis media. 8,9 The ototoxic potential of boric acid was investigated in some animal studies, and results revealed a tympanic membrane toxicity of 4% boric acid in 70% alcohol. 8,9,10 Microbiological studies showed that applying acid to an infected surface lowers pH and negatively affects bacterial growth.…”
Section: P R O V I S I O N a L L Y A C C E P T E D F O R P U B L I C ...mentioning
confidence: 99%
“…4,5,6 However, boric acid is potentially toxic, particularly if it is ingested or systematically absorbed. [7][8][9][10][11][12][13] In addition to being non-soluble in water, elemental boron has limited industrial applications, and no study has cited its potential antifungal activity. By contrast, several studies have described the antimicrobial and antifungal properties of boric acid and boron compounds [8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…We read with interest the review by Adriztina et al [1] regarding the efficacy and toxicity of boric acid in the treatment of patients with chronic suppurative otitis media (CSOM). The authors focused on the safety of boric acid at higher concentrations than those recommended for human use.…”
mentioning
confidence: 99%
“…Moreover, it is reported to be effective in the treatment of patients with CSOM, especially at a high concentration [4,5]. Although the safety of a 4% boric acid solution prepared in distilled water vs. boric acid solution in 70% alcohol, is shown in animal studies [1,6], its safety for use in humans remains unknown. We are in agreement with the view of Adriztina et al that further studies are required in patients with CSOM to evaluate the treatment outcomes of boric acid and its associated ototoxicity at high concentrations [1].…”
mentioning
confidence: 99%